Image Processing for Spider Classification - Ticay-Rivas, Jaime R.; Pozo-Baños, Marcos del; Gutiérrez-Ramos, Miguel A.; Eberhard, William G.; Travieso, Carlos M.; Jesús, Alonso B. (IntechOpen, 2012)
None